Progress and challenges of mesoporous catalysts in upgraded pyrolysis of biomass for biofuel production - Ahmad Zamri M.F.M.; Hassan S.H.A.; Tiong S.K.; Milano J.; Bahru R.; Fattah I.M.R.; Mahlia T.M.I. (Elsevier B.V., 2025)
Driven by the depletion of fossil fuels, there is a pressing need for clean alternative fuels for energy applications. Biomass pyrolysis, utilizing biomass as a feedstock, has emerged as a promising sustainable alternative. However, the presence of oxygen-containing compounds and high acidity in the biofuel produced through pyrolysis necessitate further upgrading. Mesoporous catalysts, with their high surface area, tunable pore size, and catalytic activity, have shown great potential in improving the quality of biofuels derived from biomass pyrolysis. This review explores the recent advancements and challenges associated with employing mesoporous catalysts in the upgraded pyrolysis of biomass for biofuel production. It delves into the various types of mesoporous catalysts utilized and the catalytic mechanisms at play during the upgrading process. The review further discusses the progress made and the challenges encountered in the application of mesoporous catalysts. Strategies to enhance catalyst stability and activity, such as catalyst modification and the use of co-catalysts, are also examined. Additionally, the review emphasizes the critical properties of the mesoporous structure for optimal catalyst design. By providing a comprehensive overview of the current state of knowledge, this review serves as a valuable resource for researchers and practitioners interested in the development and application of mesoporous catalysts in pyrolysis for biofuel production. It highlights the promise of mesoporous catalysts while also acknowledging the challenges that need to be addressed for their successful implementation. ? 2024 Elsevier B.V.